FIGURE 14 in Taxonomy, ecology and zoogeography of the Recent species of Rhamphostomella Lorenz, 1886 and Mixtoscutella n. gen. (Bryozoa, Cheilostomata) - Grischenko, Andrei V.; Gordon, Dennis P.; Taylor, Paul D.; Kuklinski, Piotr; Denisenko, Nina V.; Spencer-Jones, Mary E.; Ostrovsky, Andrew N. (Zenodo, 2022)
FIGURE 14. Rhamphostomella curvirostrata (O'Donoghue & O'Donoghue, 1923). A, F, K. Lectotype, NHMUK 1964.1.2.7 (Pacific coast of North America, presumably Vancouver Island, British Columbia). B, C, G, H, J, L, M. ZIRAS 4/50547 (Iturup Island, Kuril Islands, Sea of Okhotsk). D, E, I. ZIRAS 1/50115 (Medny Island, Commander Islands, Bering Sea). A. Colony margin with zooids developing above sponge spicules; developing ooecia visible near lower margin of image (arrows). B. Distal view of marginal zooids, showing primary orifices with median lyrula and lateral processes. C. Details of suboral avicularium. D. Non-ovicellate zooids close to colony periphery. E. Two zooids with ooecia embedded in secondary calcification, and enlarged, deep marginal areolae separated by strongly elongate interareolar ridges. F. Frontal view of ovicellate zooid. G. Group of ovicellate zooids in older part of colony. H. Lateral view of distal part of ovicellate zooid, showing details of ooecium and suboral avicularium. I. Interior of frontal shield, showing lyrula, ring scar, and areolae. J. Internal view of orifice, showing lyrula, lateral processes and condyles. K. Basal surface of colony growing over sponge (spicules are evident). L. Interior of frontal shield, showing ring scar and exterior wall microstructure of umbonuloid component. M. Lateral view of zooid, showing ooecium, suboral avicularium and zooidal lateral wall with mural pore chambers. Scale bars: A, D, G, K, 500 μm; B, H, 250 μm; C, E, F, I, J, 100 μm; L, 50 μm; M, 200 μm. Published as part of Grischenko, Andrei V., Gordon, Dennis P., Taylor, Paul D., Kuklinski, Piotr, Denisenko, Nina V., Spencer-Jones, Mary E. & Ostrovsky, Andrew N., 2022, Taxonomy, ecology and zoogeography of the Recent species of Rhamphostomella Lorenz, 1886 and Mixtoscutella n. gen. (Bryozoa, Cheilostomata), pp. 1-115 in Zootaxa 5131 (1) on page 50, DOI:10.11646/zootaxa.5131.1.1, http://zenodo.org/record/6521113